Cardiovascular outcomes and tumour necrosis factor antagonists in chronic inflammatory rheumatic disease: a focus on rheumatoid arthritis. Issue 1 (5th December 2016) - Tocci, Giuliano; Goletti, Delia; Marino, Valentina; Matucci, Andrea; Milano, Giuseppe Maria; Cantini, Fabrizio; Scarpa, Raffaele
ABSTRACT: Introduction: Many chronic rheumatic diseases have an inflammatory etiology, leading to accelerated atherosclerosis and increased occurrence of vascular diseases. In rheumatoid arthritis (RA), a reduction in cardiovascular (CV) events has been reported under treatments reducing systemic inflammation. Areas covered: Given the central role of tumour necrosis factor alpha (TNFα) in chronic inflammatory conditions and in atherosclerosis, it has been suggested that TNFα-antagonists may reduce CV risk and mortality. Although there are no randomized controlled or head-to-head trials investigating the effect of specific anti-TNF-agents on CV outcomes, observational cohort studies, national registry data, and meta-analyses in RA have reported improved CV outcomes with anti-TNF therapy. Expert opinion: It is unclear whether this is due to reduced systemic inflammation or a specific anti-TNF effect at the atherosclerotic plaque level. Observed CV benefits appear to correlate with anti-TNF response. Conversely, although inconsistently, anti-TNF agents have also been linked with increased incidence/worsening of heart failure. Additional CV adverse events with anti-TNFs include vasculitis and venous thromboembolic events. We provide an overview of the likely effects of anti-TNF therapy on CV risk and adverse events, and evaluated differences in CV outcomes among different anti-TNF-agents.